Can palatal splint improve stability of segmental Le Fort I osteotomies? - Parizotto, Julianna Oliveira Lima [UNESP]; Borsato, Karina Tostes [UNESP]; Peixoto, Adriano Porto; Bianchi, Jonas [UNESP]; Cassano, Daniel Serra; Gonçalves, João Roberto [UNESP] (Wiley, 2020)
Objectives: The purpose of this study was to evaluate the influence of a palatal splint on stability in multi-segment maxillary osteotomies. Setting and Sample Population: Retrospective series of fifty-one adult patients, consecutively operated with bilateral sagittal split osteotomy (BSSO) and three-piece maxillary osteotomies, divided according to the use of a palatal splint (Group 1, n = 30) or no palatal splint (Group 2, n = 21). Materials and Methods: Maxillary surgical casts (T1) and post-retention casts (T2), taken at least six months after discontinuation of orthodontic retention, were digitized (MicroScribe-3DX), measured and compared. Fifty-one landmarks were identified on the maxillary, transverse dimension changes and arch length were calculated. Longitudinal changes in all measurements were assessed by t test. Results: Post-surgical transverse instability in group 1 ranged from 0.3 ± 0.4 to −1.3 ± 0.2 mm and was statistically significantly smaller than in group 2 that ranged from −1.0 ± 0.3 to −2.5 ± 0.5 mm. Conclusions: The use of a palatal splint after segmental Le Fort I maxillary osteotomy improved transverse stability in the posterior region. The post-surgical transverse instability occurred only between canine gingival points and thus suggesting no clinical relevance.
Keywords: le fort; orthognathic surgery; osteotomy; segmental Le Fort I osteotomy; stability